Integrating ESG into the Management Control Systems at Sinhan Bank Indonesia - Tansil, Dance; Daromes, Fransiskus Eduardus; Bangun, Yakobus Kaditti (Magister Akuntansi - Universitas Atma Jaya Makassar, 2026)
This study aims to analyze how PT Bank Shinhan Indonesia integrates Environmental, Social, and Governance (ESG) principles into its Management Control System (MCS) to achieve sustainable performance. A qualitative approach with an exploratory study method is used to explore the sustainability integration process in MCS through in-depth interviews with seven key informants from various strategic departments, as well as document analysis such as sustainability reports and internal bank policies. This study is based on institutional theory, focusing on mimetic, coercive, and normative pressures as drivers of MCS change. Eight control indicators studied include planning, policy, operational, employee, customer, product and service innovation, Key Performance Indicator (KPI), and culture. The results show that Bank Shinhan Indonesia has adopted an ESG strategy through internal policies, green product innovation, strengthening sustainability-based KPIs, and embedding ESG values ??into the organizational culture.